Evaluation of the impact of universal screening for gestational diabetes mellitus on maternal and neonatal health outcomes. (7th June 2011) - Farrar, D; Wright, J; Whitelaw, D; Tuffnell, D
Abstract : Background: Rates of gestational diabetes mellitus (GDM) are increasing. Treatment seems to reduce perinatal mortality and morbidity, 1 however the impact on outcomes of alternative strategies for both screening and diagnosing GDM are unclear. The aim of this study was to evaluate the impact on health outcomes of a change from selective to universal screening. Methods: Data were compared for the 3 years before and after universal screening and are presented as rate ratios (RR) for percentages of all births and births to women with GDM. Births in 2007 were excluded as they included a mixture of women who had been selectively and universally screened. Results: Women diagnosed with GDM increased significantly, RR 3.78 (CI 3.31 to 4.33), as did induction of labour for all births, RR 1.43 (CI 1.35 to 1.50) and for GDM births, 1.21 (CI 1.0 to 1.49). For all births, caesarean RR was unaffected, 1 (CI 0.96 to 1.05), but reduced for GDM births, 0.7 (CI 0.57 to 0.87). Admissions to the neonatal unit decreased significantly for all births, RR 0.82 (CI 0.77 to 0.88) and GDM births, 0.43 (CI 0.32 to 0.59). RR of infants greater than 4 kg for all births was unaffected, 1.04 (CI 0.95 to 1.12), but reduced significantly for GDM births, RR 0.25 (CI 0.16 to 0.37). Conclusion: Universal screening significantly increased the identification of women with GDM. Although induction of labour increased this did not lead to an increase in caesarean birth. Universal screening seemed to improve perinatal outcomes; however increased identification of those women with less severe disease may lower adverse outcome rates for GDM births.